Urinary Ascites: Cryptic Presentation of Unrecognized Urinary Bladder Injury - Ananna, Mehruba Alam; Ahmed, M Ashrafuddin; Haque, WMM; Ahmed, Ziauddin (BIRDEM Medical Journal, 2012)
A case of urinary ascites in a 37-year-old woman caused by an unrecognized bladder injury inflicted during hysterectomy done seven months earlier is presented here. The site of injury was located by conventional retrograde cystography and repaired by laparotomy. The medical record suggesting uneventful peri and postoperative period, absence of expected typical changes in serum biochemistry and the unusual aetilogy of the ascites led to the delay in the diagnosis. The case demonstrates the importance of high index of suspicion of bladder injury following pelvic surgery in patients with ill-defined symptoms and unexplained ascites even in the absence of typical biochemical changes. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12364 Birdem Med J 2012; 2(1) 60-62